A STUDY ON GENDER PERCEPTIONS IN NORTHERN CYPRUS TURKISH COMMUNITY - Mamuk, Rojjin; Payas, Ayse; Kemalogullari, Zeynep; Fırat, Özcan; Güles, İbrahim Halil (My University, 2022)
This cross-sectional and descriptive study aims to identify the gender perception and the affecting factors in individuals from Northern Cyprus. The sample of the study included 304 participants, and the data were collected through the Socio-demographic Form and the Perception of Gender Scale. Statistical analyses showed that the participants’ “Perception of Gender Scale” mean score was 89,08±16,28. The analysis results also showed that gender perceptions were more positive in women compared to men (p<0.001), in individuals living in İskele compared to the ones living in Yeşilköy (p=0.003), in individuals who lived in the city the longest period compared to the ones lived in the village (p=0.024), in single people compared to married people (p=0.015), and in those aged 25 and below compared to those aged 36 and above (p=0.002). Gender perception also was found to be lower in individuals who had four and more siblings (p=0.022), but it was found to be higher in those who had only girls as siblings (p=0.033). On the other hand, the gender perception of the individuals who had an education level of university and above was higher than the participants who had other education levels (p<0.001). Also high education level of the parents had an positive effect on the gender perception of the individuals (p<0.001). The results of this study showed that although the participants’ gender perception was not very high, it was positive and was affected by many factors.
Keywords: Gender; perception; woman; Cyprus; gender equality